2019
DOI: 10.3928/01913913-20190923-03
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Effect of General Anesthesia on the Pediatric Patient

Abstract: In this article, the authors review the animal and human data on the recent studies looking at the neurotoxicity of general anesthesia in the pediatric population. Animal studies in rodents and non-human primates demonstrate neurotoxic effects when exposed to general anesthesia at a young age. However, prospective clinical studies in humans do not show significant differences in intelligence quotient outcomes in children younger than 3 years with isolated and/or short exposures. Current studies are investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…While animal models have shown neurotoxicity associated with anesthetic exposure, clinical studies have not shown a difference in neurocognitive behavior or IQ when patients younger than 3 years of age have short exposures to anesthesia. [28][29][30] While it appears the benefits of casting outweigh the risks of anesthesia, we need to continue to be mindful about the Copyright @ 2021 JPOSNA www.jposna.org potential negative impact of continued exposure and try to minimize this as much as possible.…”
Section: Downsides Of Castingmentioning
confidence: 99%
“…While animal models have shown neurotoxicity associated with anesthetic exposure, clinical studies have not shown a difference in neurocognitive behavior or IQ when patients younger than 3 years of age have short exposures to anesthesia. [28][29][30] While it appears the benefits of casting outweigh the risks of anesthesia, we need to continue to be mindful about the Copyright @ 2021 JPOSNA www.jposna.org potential negative impact of continued exposure and try to minimize this as much as possible.…”
Section: Downsides Of Castingmentioning
confidence: 99%